Prevalence of bisphosphonate associated osteonecrosis of the jaws in multiple myeloma patients - Walter, Christian (BioMed Central, 2010)
BACKGROUND: Bisphosphonate-associated osteonecrosis of the jaws (BP-ONJ) is an adverse effect of bisphosphonate treatment with varying reported incidence rates. METHODS: In two neighboring German cities, prevalence and additional factors of the development of BP-ONJ in multiple myeloma patients with bisphosphonates therapy were recorded using a retrospective (RS) and cross-sectional study (CSS) design. For the RS, all patients treated from Jan. 2000 - Feb. 2006 were contacted by letter. In the CSS, all patients treated from Oct. 2006 - Mar. 2008 had a physical and dental examination. Additionally, a literature review was conducted to evaluate all articles reporting on BP-ONJ prevalence. PubMed search terms were: bisphosphonat, diphosphonate, osteonecrosis, prevalence and incidence. RESULTS: In the RS, data from 81 of 161 patients could be obtained; four patients (4.9%) developed BP-ONJ. In the CSS, 16 of 78 patients (20.5%) developed BP-ONJ. All patients with BP-ONJ had received zoledronate; 12 of these had had additional bisphosphonates. All except one had an additional trigger factor (tooth extraction [n = 14], dental surgical procedure [n = 2], sharp mylohyoid ridge [n = 3]). CONCLUSION: The prevalence of BP-ONJ may have been underestimated to date. The oral examination of all patients in this CSS might explain the higher prevalence, since even early asymptomatic stages of BP-ONJ and previously unnoticed symptomatic BP-ONJ were recorded. Since nearly all patients with BP-ONJ had an additional trigger factor, oral hygiene and dental care might help to reduce BP-ONJ incidence.